UANG DAN KEKUASAAN POLITIK - Siti Isnaini Nurul Wahidah (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2017)
Vote buying is abnormal politic but is massive practice in Indonesian General Election. Curriculum vitae and professional popularity was substitute with money and goods. With observation, interview, and documentary technique this article assumed there are not something new in vote buying practices in Indonesian politics.